2004
DOI: 10.1007/s00251-003-0635-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genomic and expressed major histocompatibility class�Ia and class�II genes in a hexaploid Lake Tana African ?large? barb individual (Barbus intermedius)

Abstract: Expression of too many co-dominant major histocompatibility complex (MHC) alleles is thought to be detrimental to proper functioning of the immune system. Polyploidy of the genome will increase the number of expressed MHC genes unless they are prone to a silencing mechanism. In polyploid Xenopus species, the number of MHC class I and II genes has been physically reduced, as it does not increase with higher ploidy genomes. In the zebrafish some class II B loci have been silenced, as only two genomically bona fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 39 publications
3
28
0
1
Order By: Relevance
“…Different class IIA numbers were also found in other fish species, such as two loci have been found both in trout and half-smooth tongue sole Xu et al 2009). More than four alleles of MHC class IIB have also been identified in one single individual in other fish species, which also suggested the existence of at least three loci of class IIB (Kruiswijk et al 2004;Chen et al 2006;Xu et al 2009;. Real-time PCR analysis demonstrated that the spotted halibut MHC IIA and IIB mRNA were expressed in all tested tissues, with high expression in the kidney, spleen, and gill.…”
Section: Discussionmentioning
confidence: 91%
“…Different class IIA numbers were also found in other fish species, such as two loci have been found both in trout and half-smooth tongue sole Xu et al 2009). More than four alleles of MHC class IIB have also been identified in one single individual in other fish species, which also suggested the existence of at least three loci of class IIB (Kruiswijk et al 2004;Chen et al 2006;Xu et al 2009;. Real-time PCR analysis demonstrated that the spotted halibut MHC IIA and IIB mRNA were expressed in all tested tissues, with high expression in the kidney, spleen, and gill.…”
Section: Discussionmentioning
confidence: 91%
“…The characteristics of ORF and the deduced proteins of highly polymorphic MH class II A genes from half-smooth tongue sole were all similar to those from other species (van Erp et al, 1996;Hardee et al, 1995;Cuesta et al, 2006;Stet et al, 2002;Kruiswijk et al, 2004;Zhang and Chen, 2007;Yu et al, 2009). The 25 alleles in half-smooth tongue sole could noticeably be clustered to two groups with distinct amino acid sequences, which indicated that the two groups of alleles belonged to two different genes.…”
Section: Discussionmentioning
confidence: 73%
“…All the 200 individuals in the challenge test consisted of two A genes, and different conserved amino acids in specific positions were observed in their alleles. Similarly, two or more class II A genes in other teleost have been reported, such as the two linked genes (Gaac-DAA and Gaac-DBA) in three-spined stickleback (Reusch et al, 2004), two linked groups DAA and DBA/DCA in Peacock cichlid (Murray et al, 2000), two genes in channel catfish (Godwin et al, 2000;Quiniou et al, 2005), four genes in large barb (Kruiswijk et al, 2004) and Atlantic salmon (Harstad et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…In 1990, Hashimoto et al reported the first MHC genes in the common carp (Cyprinus carpio). Since then, class I, class IIa and class IIb genes have been identified in a large variety of cyprinid species Kruiswijk et al 2002Kruiswijk et al , 2004Ottová et al 2005;Takeuchi et al 1995;van Erp et al 1996). Data obtained were compared with the patterns of genetic variability revealed previously by RAPD and mitochondrial DNA (mtDNA) genetic markers (Mamuris et al 2005) in order to determine the extent that genetic drift and natural selection may shape genetic variation at MHC loci in this endemic species and to develop conservation rationale.…”
Section: Introductionmentioning
confidence: 99%